Growth Performance and Economic Analysis of Indian Major Carps and Tilapia in Rainwater Ponds - Pandey, Pramod K; Sethi, Laxmi N; Pholane, Limbraj P; Panda, Sudhindra N; Pandey, Vinay K; Biswas, Sagor; Soupir, Michelle (Fishery Technology, 2025)
Enhancing water resources is crucially important for improving food production in rainfed regions. The income of rural people in these regions is mainly tied with water availability. One option is disseminating rainwater harvesting for conserving rainwater and utilizing it for food production. Here we propose a rainwater harvesting method, which helps to conserve rainwater in the rainy season, provide water storage for rearing fish and facilitate supplemental irrigation to crops in the dry season. To verify the suitability of rainwater harvesting approach for improving food production and rural income, here we conducted a field study, which involved designing rainwater harvesting ponds (lined and unlined), storing rainwater and water recycling for irrigating crops. The growth of Catla catla, Labeo rohita, Cirrhinus mrigala, and tilapia in lined and unlined rainwater harvesting ponds was assessed and the resulting benefits were calculated under various scenarios. Water quality measurements showed the suitability of water stored in both rainwater harvesting ponds for fish culture. The Specific Growth Rates (SGR) of all the species in the lined ponds were greater than the unlined ponds except SGR of C. mrigala. Results show that the fish culture in the ponds improved the annual net benefit of rainwater harvesting systems. Forestimating Internal Rate of Return (IRR) and Net Present Value (NPV), the cost and benefits of the rice-fish integration was inflated using Consumer Price Index (CPI) data of 2001-2002 and 2011-2012. Unlined and lined ponds with fish culture produced annual net benefits of 118 and 188% of that without fish culture. The IRR in unlined and lined pond rainwater harvesting systems without fish rearing were 9.5 and 9.0%, while with fish culture these values increased to 13 and 26%, respectively. We anticipate that the research presented here demonstrates the potential benefits of the rainwater harvesting system and will enhance water resources in rainfed regions.